Menelisik Efektivitas Sistem Hukum Kesehatan: Sebuah Evaluasi Strategis Terhadap Kebijakan Publik Dan Implementasinya Di Indonesia - Wahyuni, Ruslina Dwi; Rashed, Azhar Rashed; Windari, Windari (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2025)
This article aims to discuss the analysis of an effective health legal system with a focus on policy evaluation and implementation strategies. The health sector in Indonesia has a very important role in people's lives that affect people's welfare. However, this sector also faces various challenges related to services including policies, regulations, and implementation. This study uses a qualitative approach with literature studies and document analysis, which includes laws and regulations such as Law Number 36 of 2009 concerning Health, Law Number 52 of 2009 concerning Population Development and Family Development, Presidential Regulation Number 72 of 2012 concerning the National Health System. The results of the study show that although legal regulations related to family planning policies are quite complete, implementation in the field still faces various obstacles such as challenges including budget constraints, inadequate transportation infrastructure in remote areas, and lack of public awareness of the importance of using contraceptives. The results of this study provide recommendations for the need to increase the budget for the health sector to expand the reach of services, develop training programs for medical personnel so that they are better prepared to face challenges in the field, conduct more intensive public awareness campaigns to change public views on family planning, strengthen the monitoring system so that each intervention can be evaluated in a timely manner.